1997
DOI: 10.1002/(sici)1096-9063(199702)49:2<169::aid-ps520>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation ofs-Triazine Herbicides and Related Degradation Products in Liquid Cultures by the White Rot FungusPhanerochaete chrysosporium

Abstract: The ability of the white rot basidiomycete Phanerochaete chrysosporium to transform s‐triazine herbicides has been investigated in laboratory experiments. The chlorinated metabolites formed during atrazine N‐dealkylations were not further transformed by the fungus, whereas hydroxy‐atrazine was converted to an unknown product. P. chrysosporium was also able to carry out the N‐dealkylation of the herbicides simazine, propazine and terbuthylazine. Herbicide metabolism was not supported by purified peroxidases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Previous research found that atrazine degradation by Phanerochaete chrysosporium and Pleurotus ostreatus INCQS 40310 had a proportional dependence on biomass and associated enzymes [4,15,16]. Thus, a nutrient rich culture medium, allowing substantial biomass development, provides best results in terms of biodegradation [22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous research found that atrazine degradation by Phanerochaete chrysosporium and Pleurotus ostreatus INCQS 40310 had a proportional dependence on biomass and associated enzymes [4,15,16]. Thus, a nutrient rich culture medium, allowing substantial biomass development, provides best results in terms of biodegradation [22].…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, fungal biodegradation is based on oxidative-hydrolytic mechanisms and until now, the metabolic routes identified are more diverse. Fungi usually modify the molecule by sequentially removing aromatic ring substituents, with dealkylation as first step [15,16]. The resulting metabolites, such as deethylatrazine (DEA), deisopropylatrazine (DIA), deethyldeisopropylatrazine (DEA-DIA), and hydroxyatrazine (HA) still retain the aromatic ring [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It might be assumed that it would be the ligninolytic system that attacks trifluralin (laccases and/or peroxidases), since these have been implicated in the attack on other nitroaromatics, but these fungi also contain diverse other degradative enzymes such as cytochrome p450s, which could alternatively be involved . Interestingly, both fungal and bacterial p450 enzymes are known to catalyze N -dealkylation reactions similar to those seen in many studies on trifluralin biodegradation, and thus it is possible that p450s play a role in trifluralin degradation in pure cultures and in the field. Further studies are required to confirm this.…”
Section: Biodegradation Of Trifluralin By Pure Cultures Of Microbesmentioning
confidence: 91%
“…Aqueous phases were pooled prior to HPLC analysis. Aliquots (10 ml) were filtered on a Whatman GF/D prefilter and concentrated on a C18 guard column as described previously [5].…”
Section: Analytical Procedures For Pah Compoundsmentioning
confidence: 99%